DIFFERENCE EQUATION FOR AUSTRALIAN SHEEP BLOWFLIES GROWTH - Gisbtarani, J I; Huda, M N; Setiyaningsih, H; Solikhatun, Solikhatun (PATTIMURA UNIVERSITY, 2024)
The population of Australian sheep blowflies, Lucilia cuprina, in Australia is of concern to many researchers because it causes several problems. These problems occur in the sheep industry where there is a term